Upaya Pemberdayaan Petani Gula Semut Melalui Sertifikasi Organik Desa Pasinggangan Kecamatan Banyumas Kabupaten Banyumas - Nur Alifah; Ageng Widodo (UIN Siber Syekh Nurjati Cirebon, 2021)
During the pandemic, many people have lost their jobs. With the loss of their jobs, they return to their hometowns to farm. The return of the community to the village is not supported by adequate agricultural conditions. So that the welfare of farmers is less guaranteed. This also happens to coconut sugar farmers. The relatively cheap price of printed sugar makes it necessary to empower ant sugar certification. Certification is carried out to maintain the quality of the sugar produced. This is because the community has not produced sugar according to standards. The method used is a qualitative research method with a participatory approach. The results of the research carried out were first, the community was given an assessment and knowledge about the processing of ant sugar in accordance with standards both from the process and equipment. second, in the implementation there are obstacles in the form of many farmers using chemicals, the community's mindset has not been developed regarding the benefits of ant sugar, and the existence of a home industry that accommodates printed sugar so that people prefer to sell it to the industry.